Diagnostic Value of Sodium, White Blood Cell, Neutrophil Levels; White Blood Cell/Sodium and Neutrophil/Sodium Ratios in Appendicitis in Pediatric Patients - Cem Kaya; Gökhan Arkan; Fatma Nur Aracıer Uçaner; Leyla Nur Türker; Alparslan Kapısız; Ramazan Karabulut; Zafer Türkyılmaz; Kaan Sönmez (Gazi Medical Journal)
Objective: Acute appendicitis is one of the most common causes of abdominal pain requiring surgical intervention in children. Although clinical and imaging modalities play a central role in disease diagnosis, laboratory markers, such as white blood cell (WBC) count, neutrophil count, and electrolyte disturbances, particularly sodium levels, have been explored as potential indicators of disease severity. This study aimed to evaluate the relationship between serum sodium levels, WBC and neutrophil counts, and their respective ratios with the diagnosis and severity of appendicitis. Methods: This retrospective analysis included 176 pediatric patients who underwent appendectomy. Patients were divided into three groups based on pathological findings: Group 1 (non-appendicitis, n=59), group 2 (acute appendicitis, n=82), and group 3 (perforated appendicitis, n=35). WBC, neutrophil, and sodium levels were recorded. ANOVA and post-hoc Tukey’s tests were used to assess differences between groups. A logistic regression model was employed to evaluate the combined ability of WBC, neutrophil, and sodium levels to distinguish group 1 from groups 2 and 3, and the model’s performance was evaluated using the area under the ROC curve (AUC). Results: Significant differences were observed between group 1 and groups 2 and 3 regarding WBC (p<0.001), neutrophil (p<0.001), and sodium levels (p<0.001). Group 3 had the highest WBC count (17,123±4,491 cells/µL) and the lowest sodium levels (132.5±1.4 mEq/L), whereas group 1 had the lowest WBC count (10,660±3,804 cells/µL) and the highest sodium levels (137.5±2.6 mEq/L). Logistic regression analysis of the combined WBC, neutrophil, and sodium values obtained an AUC of 0.703, indicating moderate diagnostic utility. Conclusion: This study demonstrated that WBC count, neutrophil count, and sodium level, as well as their ratios, can aid in diagnosing appendicitis in pediatric patients. Although sodium levels were significantly lower in patients with appendicitis, no significant difference was found between acute and perforated appendicitis. The WBC/sodium and neutrophil/sodium ratios could be valuable in clinical practice, especially for distinguishing between appendicitis and non-appendicitis cases. Further research is warranted to explore their utility in larger populations.